“The Rules of Engagement”: Student Engagement and Motivation to Improve the Quality of Undergraduate Learning - Senior, Rowena M.; Bartholomew, Paul; Soor, Avita; Shepperd, Dan; Bartholomew, Nicola; Senior, Carl (Frontiers in Education, 2018)
Studying at university continues to grow in popularity and the modern-day university has expanded considerably to meet this need. Invariably as such expansion occurs pressures arise on a range of quality enhancement processes. This may have serious implications for the continued delivery of high quality learning experiences that both meet the expectations of incoming students and are appropriate to their postgraduation aspirations. Ensuring students become active partners in their learning will encourage them to engage with a range of quality enhancement processes. The aim of the current work is to examine the various factors that motivate students to engage in such a fashion. Three focus groups were carried out in a stratified manner to ascertain student motivations and to triangulate an effective set of recommendations for subsequent practice. The participants consisted of engaged and non-engaged first year undergraduate students as well as student-facing staff who were asked to comment on their experiences as to why students would want to engage as a course representative. Nominal group technique was applied to the emerging thematic data in each group. Three key motivational themes emerged that overlapped across all focus groups i.e., a need for individual representation that makes a change, a desire to develop a professional skillset as well as a desire to gain a better understanding of their course of study. A university that aligns its student experience along these themes is likely to facilitate student representation. As is standard practice recommendations for future work are described alongside a discussion of the limitations.